The effects of auditory directional cues on task performance and cognitive load in virtual reality for middle-aged adults. - Yeh, PoChan; Wu, YiTing (Journal of Bodywork & Movement Therapies, 2025)
As immersive technologies become increasingly prevalent in healthcare and cognitive training, ensuring their accessibility for aging populations has emerged as a critical design priority. This study investigates the impact of auditory directional cues on spatial navigation performance and perceived task workload among middle-aged adults within a virtual reality (VR) maze environment. A total of 64 participants, aged 45 to 65, were randomly assigned to either an experimental group (with auditory cues) or a control group (without auditory cues). Results indicated that participants receiving auditory support completed tasks significantly faster and reported lower subjective cognitive workload, as measured by the NASA Task Load Index (NASA-TLX). Although task completion rates and System Usability Scale (SUS) scores did not reach statistical significance, both showed favorable trends for the auditory group. Furthermore, gender-based analyses revealed that auditory guidance may help reduce performance disparities, particularly benefiting individuals with lower baseline spatial confidence. Building on these findings, the study offers not only theoretical insights into multisensory design but also practical implications for the development of age-inclusive VR systems in healthcare and rehabilitation. Design recommendations include the integration of directional audio to support spatial decision-making, the implementation of multimodal feedback to reduce cognitive demand, and the development of personalization features to foster greater inclusivity and long-term user engagement in immersive therapeutic environments.